Scene From The Birth Of Venus: Kajian Karya Fotografi - Locita, Agra (Capture : Jurnal Seni Media Rekam, 2011)
Scene From The Birth Of Venus is a photographic artwork that created in 1949. The artwork was the result of collaboration between Salvador Dali and two photographers, Baron George Hoyningen-Huene and George Platt Lynes. They created Birth of Venus differently with first painting whom created by Bottocelli Sandro. He depicted the goddess Venus graceful and shy, but it recreated by Salvador Dali in an imaginative photographic artwork. In Scene From The Birth Of Venus, the goddess Venus depicted as half human and fish. Two creations in different way but still in the birth of the goddess Venus theme. Key words: photography, painting, imaginative